The Relationship between Personality Factors, Social Support, and Regulation with Lifestyle - Masoud Ferdosi; Behnaz Nikkar Isfahani; Mohammad Shayan Kolahdozan (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Since lifestyle is a multi-dimensional concept and various dimensions of health or disease are affected by each other, the measures taken to promote health should pay attention to all aspects of individual physical, mental, spiritual health, as well as the general health of society. The present study aimed to investigate the relationship between psychological components including personality factors, social support, and regulation with lifestyle among obese individuals. Methods: This study was analytical in terms of purpose and cross-sectional in terms of time and was conducted in 2018. In this study, the individuals referring to the health centers of Isfahan were considered as the research population. A number of 357 individuals randomly entered the study. Data collection was based on the perceived social support questionnaire of Zimet et al., health promoting lifestyle questionnaire of Walker, the CERQ emotion cognitive regulation questionnaire, and Neo five-factor inventory. Data were analyzed by SPSS18 using independent T-test, Pearson correlation, and ANOVA. Results: In the final model, a significant relationship was found between gender, nervousness, extroversion, openness, conscientiousness, social support, and health promoting lifestyle (P-value < 0.05). In addition, a significant relationship was observed between marital status, nervousness, extroversion, openness, agreement, and social support (P-value < 0.05). A significant relationship was observed between personality factors and health promoting lifestyle. Such a relationship in nervousness was inverse and significant while it was positive and significant in extraversion, openness, and conscientiousness (P-value < 0.05). Based on the results, there was an inverse relationship between social support and lifestyle and also between regulation and lifestyle (P-value < 0.05). Conclusion: In order to take motivational measures for changing the lifestyle of obese individuals, it is recommended to regard the psychological factors and their relationship to increase the effectiveness of interventions.